2003
DOI: 10.1103/physrevlett.90.216109
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Observation of Temperature and Pressure Driven Preroughening and Roughening

Abstract: Preroughening and roughening transitions are observed on the GaAs(001) surface using scanning tunneling microscopy. By tuning the substrate temperature or As4 pressure the surface morphology can be made free of islands, covered with one monolayer high islands or covered with islands on top of islands forming a wedding-cake-type structure. These three distinct surface morphologies are classified as ordered flat (OF), disordered flat (DOF), and rough within the restricted solid-on-solid model. Here, the DOF phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The agreement with this simple KPZ continuum model suggests that the anomalous effects associated with the singular free energy of crystal facets are not important for the growth conditions in question [4]. This is likely a consequence of the fact that under our growth conditions the surface is above the roughening temperature [11].…”
Section: Conventional Modeling Of Weak Surface Texturesupporting
confidence: 60%
“…The agreement with this simple KPZ continuum model suggests that the anomalous effects associated with the singular free energy of crystal facets are not important for the growth conditions in question [4]. This is likely a consequence of the fact that under our growth conditions the surface is above the roughening temperature [11].…”
Section: Conventional Modeling Of Weak Surface Texturesupporting
confidence: 60%
“…Notice that this coverage varies from 80 to 40% as the substrate temperature is increased. Reprinted from [165], Copyright (2003) by the American Physical Society. been measured as a function of coverage and displayed a non-systematic variation between 2 and 3 [163].…”
Section: Role Of Strain On Island Shapementioning
confidence: 96%
“…In a series of similar but more extensive experiments, LaBella et al measured the surface morphology using in situ STM for GaAs(0 0 1) surfaces that were annealed using band edge temperature control and then quenched to room temperature [162,31,18,[163][164][165][166]. An exhaustive study of the accessible phase space was performed which included temperature ranges from 500 to 700 C, As 4 BEPs ranging from 0.01 to 10 mTorr and annealing times from 1 min to 33 h. These studies determined that the phase transitions and surface morphologies observed were consistent with the framework of the den Njis model.…”
Section: Theoretical Models Of Surface Rougheningmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the coupled two-state nature of graphene ripples and their potential for collective behavior, the celebrated and versatile Ising model might, in principle, be applicable. While Onsager's famous 2D solution was initially applied to the spontaneous magnetization of a 2D square lattice ferromagnet [11,12], through group renormalization [13] it has been established that a wide range of systems belong to the 2D spin-half Ising universality class [14][15][16][17][18][19][20][21]. Bonilla and Carpio treated graphene's individual carbon atoms with the 2D Ising model [22,23] and reproduced the existence of ripples [24,25].…”
Section: Introductionmentioning
confidence: 99%